Contemporary Architecture in Southeast Asia: A Case Study of Spine Architects in Myanmar - Nyunt, Kyaw San; Fusinpaiboon, Chomchon (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
Southeast Asia’s contemporary architecture has been evolving alongside the region’s recent developments. However, the contexts of some Southeast Asian countries, for instance, Myanmar, were often overlooked in the analyses of the region’s contemporary architecture. By examining the works of one of the country's leading local firms, Spine Architects, this paper investigates how Myanmar’s contemporary architecture was shaped between 2000 and 2010. The paper analyses Spine Architect’s selected works together with relevant literature reviews and a relation with political, economic, and social issues of Myanmar within the selected time frame. The study reveals that a leading local architect firm’s contemporary design considerations can flourish alongside its peers at the international level, and keep pace with regional contemporary architecture developments, even under the challenges and limitations of a nation. The paper also fills a gap in contemporary Asian architecture discourse and shows the architectural profession’s simultaneous intermingling with and detachment from political, economic, and social contexts.